Improved Lagrangian bounds and heuristics for the generalized assignment problem - Litvinchev, I. [UNESP]; Mata, M. [UNESP]; Saucedo, J. [UNESP]; Rangel, S. [UNESP] (Pleiades Publishing, 2017)
Modified Lagrangian bounds are proposed for the generalized assignment problem. The approach is based on a double decomposable structure of the formulation. A family of greedy heuristics is considered to get Lagrangian based feasible solutions. Numerical results for problem instances with number of agents close to number of tasks are provided.